The protective underlying mechanisms of Schisandrin on SH-SY5Y cell model of Alzheimer's disease. Issue 19 (2nd October 2019) - Zhao, Zhi-Ying; Zhang, Yuan-Qing; Zhang, Yong-Hui; Wei, Xie-Ze; Wang, He; Zhang, Ming; Yang, Zhan-Jun; Zhang, Chun-Hong
ABSTRACT: The extract of Schisandrin a traditional Chinese medicine was postulated to be effective in prevention and treatment of Alzheimer's disease (AD). The aim of this study was to examine the underlying protective actions of Schizandrin using a human neuroblastoma cell line (SH-SY5Y). In particular Schizandrin-mediated effects on expression of glycogen synthase kinase (GSK)-3β, protein kinase B (Akt) and Tau protein, known to be altered in AD were determined. In preliminary assays, various concentrations of Schisandrin were incubated SH-SY5Y cells to establish effects on cell viability and potential toxicity in further experimentation. Amyloid-β (Aβ1-42 ) peptide 10 μmol/L was used to induce in vitro AD model in SH-SY5Y. Exposure to Aβ1-42 significantly reduced cell viability. Treatment with Schisandrin to Aβ1-42 exposed cells increased cell viability compared to amyloid peptide; however only the 10 μmol/L Schisandrin concentration was effective in restoring cell viability to control. Western blot analysis demonstrated that Aβ1-42 produced a significant decrease in p -Akt protein expression levels accompanied by marked elevation in p -tau and p -GSK-3β protein expression levels. Addition of 10 μmol/L Schisandrin to amyloid-treated SH-SY5Y cells was found to significantly increase protein expression levels of p -Akt associated with reduction in expression levels of p -tau and p -GSK-3β protein. Treatment with 10 μmol/L Schisandrin of SH-SY5Y cells with the p -Akt inhibitor LY294002 demonstrated that the herbal-induced rise in p -Akt protein expression was diminished by this inhibitor indicating that signal transduction occurred in the observed cellular effects. Evidence indicates that Schisandrin inhibition of Aβ1-42 -mediated cellular damage in AD neurons may involve activation of the PI3K/Akt signaling pathway where up-regulation of p -Akt activity consequently leads downstream to decreased activity of p -GSK-3β phosphorylation accompanied by reduced tau protein. Consequently, restoration of neuronal cell viability was noted. Our findings suggest that the use of Schisandrin may be considered beneficial as a therapeutic agent in AD.